Control químico de insectos chupadores en el cultivo de Guayaba (Psidium guajava L.) - Navarro Gonzáles, Fernando Andrés (2022)
This document details about the chemical control of sucking insects in the cultivation of Guava (Psidium guajava L.). The chemical control of sucking insects consists of repressing, controlling or eliminating the population of these insects in crops, through the use of chemical substances called pesticides or pesticides. The conclusions determine that the guava is a crop of economic importance, both for its fresh consumption and for the agribusiness, but for this the fruit presents excellent quality for the national and international markets, in the cultivation of guava, the losses in terms of yields and in turn that raise production costs is the presence of sucking insects, where the most prominent are white speck (Capulinia sp.) and fruit fly (Anastrepha spp.), sucking insects can be combated with the application of chemical insecticides to the plant that are absorbed by the plant and then consumed by the insect when it sucks the sap from the plant. Many of the systemic insecticides are effective for a rather long period of time, at least three weeks under favorable conditions, the management of White Speck and Fruit Fly depends mainly on prevention, management, monitoring and control strategies, especially chemical; To prevent these pests from causing economic losses, for the White Speck, the mixture of Alphacypermethrin + Chlorpyrifos is used, considered as systemic contact insecticides, they have high effectiveness to control sucking insects, in concentration, dose and application time appropriately and the fruit fly is susceptible to most insecticides, however, the authorized products for its control is malathion.